Enhancing Numeracy Literacy of Prospective Primary School Teachers through the Realistic Mathematics Education Approach in Teaching Practice - Laila Nursafitri (Ludi Litterarri, 2025)
This study examines how the Realistic Mathematics Education approach enhances numeracy literacy among prospective primary school teachers by synthesizing findings from recent empirical studies. The analysis demonstrates that RME significantly strengthens conceptual understanding, contextual reasoning, and mathematical communication by grounding instruction in meaningful real-life situations. Evidence indicates that RME promotes active engagement, higher-order thinking, and durable numeracy competence, particularly when integrated with ethnomathematics, digital tools, or project-based learning. However, the findings also highlight persistent challenges, including limited teacher readiness, difficulties in designing contextual tasks, and gaps between university instruction and school practices. These challenges underscore the need for structured coaching, curriculum alignment, and supportive institutional environments. The study concludes that enhancing numeracy literacy through RME requires comprehensive reforms across curriculum design, pedagogical strategies, and national policy frameworks. Such systemic integration ensures that future teachers acquire the professional and pedagogical skills necessary for delivering effective numeracy instruction